Determinants of Preterm Birth Among Mothers who Gave Birth at Public Hospitals in the Amhara Region, Ethiopia A Case-Control Study - Woday, Abay; MulunehID, Muluken Dessalegn; Sherif, Samiha (ResearchGate, 2019)
Background Preterm birth (PTB) is a public health issue worldwide. In developing nations, like Ethiopia, PTB is under reported and underestimated. However, it is the leading cause of neonatal and under-five mortality in Ethiopia. Besides, limited and non-comparative research studies to date has been conducted in the country to address the prevalence of PTB. Therefore, this study aims to determine predictors of PTB. Methods Hospital-based unmatched case control study was employed on a sample of 139 cases and 278 controls from October 2017 to December 2017 in the Amhara region, Ethiopia. The cases and controls were proportionally allocated in each hospital based on the last one-year case flows. As soon as a case was identified, the respective two controls were enrolled until the required sample size was satisfied. The outcome variable was measured by using either last menstrual period (LMP), early ultrasound result, or Ballard maturity examination. Faceto- face interviews were conducted using a standardized, structured, and pre-tested questionnaire to collect data. The collected data was entered into Epi-data and exported into SPSS for analysis. Independent variables with p-values < 0.25 in the bivariate analysis were entered into multivariable logistic regression models with forward logistic regressions method to control the influence of covariates. Ethical clearance was ensured. Results A total of 134 cases and 268 controls participated with a response rate of 96.4%. After adjusting for covariates, the following variables were associated with PTB: residing in rural areas [AOR = 2.99: 95% CI 1.19, 7.48], low maternal age [AOR = 3.47: 95% CI 1.11, 10.83], 4.39, 24.27]. Conclusion The study revealed maternal sociodemographic factors, short birth space, lack of antenatal care, exposure to previous adverse birth outcomes and facing medical illnesses during pregnancy were the predictors of PTB. Therefore, inclusive preventive and control interventions should be developed at regional, zonal and district levels to reduce the burden of PTB among women resided in rural areas such as integrating antenatal care services into the existing health extension packages. Study results suggest increasing the awareness of PTB, contraceptive utilization and counseling to enhance birth spacing, antenatal care visits, and accessibility to services among women in Ethiopia should be given due attention. Health care providers should focus on mothers with previous adverse birth outcomes and those exposed to medical problems during pregnancy. Additional community based longitudinal studies supplemented with qualitative methods are recommended.
Case control study
Copyright: © 2019 Woday et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Data Availability Statement: All relevant data are within the paper and its Supporting Information files.
Keywords: Preterm birth (PTB); Neonatal and under-five mortality; Last menstrual period (LMP); Ballard maturity examination